Correlations, descent measures: drift with migration and mutation. - Cockerham, C C (1987)
The analysis of gene frequencies for a nested structure of genes within individuals, individuals within subpopulations, and subpopulations within populations is considered. Alternative parameterizations are provided by measures of correlation and of identity by descent, but the latter parameters provide more flexibility. The effects of population size, mating system, mutation, and migration can be incorporated into transition equations for identity measures and the structure of equilibrium populations can be determined; the procedures are illustrated for a finite island model. With parameters defined before estimation procedures are developed, problems of estimates depending on the numbers of sampled subpopulations are avoided, while the descent measures also avoid the approximations found in other treatments.